Criteria of Activation of Powdery Materials by a Preliminary Mechanical Treatment - Mamoru Senna (KONA Powder and Particle Journal, 2014)
γ-Fe2O3 was vibration ball-milled with varying amplitude, α, from 8 to 24mm and grinding time. The enthalpy increase, ΔH*, due to mechanical treatment was measured by a differential scanning calorimeter. Pretreated sample was subsequently heated at 693K for 60min, and the fractional transformation into α-phase, a1, was obtained. Both ΔH* and a1 increased monotonically with grinding time with leveling off at longer milling time. The tendency of a level off was different, however, between ΔH* and a1. ΔH* increased monotonically with increasing amplitude whereas a1 showed a maximum at α = 10mm. The correlation between a1 and the lattice disturbance, the latter being obtained from the relative intensity of X-ray diffraction peaks, was not uniquely determined, but depended on the amplitude. This suggests that the same lattice disturbance does not always lead to the same degree of acceleration of the subsequent reaction. The reason was discussed on the basis of the content of ΔH* and the nuclei-growth mechanism of γ→α transformation of Fe2O3.